Composting behavior in Japan: an application of the theory of consumption values - Morais, Ana Catarina; Ishida, Akira (Frontiers in Sustainable Food Systems, 2025)
Ensuring effective and sustainable management of organic waste is a global challenge, especially in countries with limited land, such as Japan, where reducing, reusing, and recycling food waste is particularly crucial. The present research used the theory of consumption values (TCV) to investigate the main factors that encourage Japanese households to engage in composting. The hypotheses were evaluated using ordinal partial least squares structural equation modeling (OrdPLS). The model results suggest that household composting in Japan is influenced by social approval (social value), the visibility of the behavior and existing knowledge about composting (epistemic value), convenience (functional value), interest in gardening or farming, and an individual’s availability to participate (conditional value). Factors such as emotions (emotional value), gender, type of housing, and household size did not significantly impact the practice of household composting. Both positive and negative functional aspects of composting were found to significantly affect perceptions of convenience, thereby indirectly influencing the decision to compost. The findings suggest that promoting ongoing training and support, improving convenience, and linking household composting with urban farming, community gardens, or public spaces could enhance participation, even among those who do not garden.